Genotypic variation in tree growth and selected flavonoids in leaves of Cyclocarya paliurus. Issue 1 (2nd January 2018) - Cao, Yanni; Deng, Bo; Fang, Shengzuo; Shang, Xulan; Fu, Xiangxiang; Yang, Wanxia
Abstract : Cyclocarya paliurus is a valuable medicinal tree species in China. However, limited information is available on its genotype selection and cultivation for improvement of growth and health-promoting phytochemicals. To contribute to improved knowledge of the potential use of the species, 33 families of C. paliurus were assessed with respect to genotype on growth and flavonoid content in the leaves, and the relationship between growth and flavonoid accumulation was examined. Growth and flavonoid content varied significantly among different families, and isoquercitrin was the main component of the individual flavonoids, followed by kaempferol and quercetin. Both total and individual flavonoids showed seasonal variation, with the mean highest contents of quercetin and isoquercitrin in July but the highest kaempferol content in October. Correlation analysis showed that tree height and diameter at breast height of C. paliurus were negatively correlated with the contents of quercetin and kaempferol in the leaves, whereas no significant correlation between tree growth and total flavonoid content was detected. Hierarchical cluster analysis based on the parameters of tree growth and leaf flavonoid contents indicated that 33 families of C. paliurus were classified into four distinct groups. Results from this study are valuable for identifying superior families for a specific site and provide a basis for C. paliurus breeding strategies for flavonoid production.